The Orbits of Uranus, Its Satellites and Rings, the Gravity Field of the Uranian System, and the Orientation of the Poles of Uranus and Its Satellites - Robert A. Jacobson; Ryan S. Park (The Astronomical Journal)
R. A. Jacobson determined the orbits of the Uranian satellites, the masses of Uranus and its satellites, and the orientation of the pole of Uranus from Earth-based astrometry, Earth-based ring occultations, and observations acquired with the Voyager 2 spacecraft. Subsequent to that publication, several observers obtained new astrometry, and some of the original astrometry was rereduced against the Gaia star catalog. Moreover, R. G. French et al. made a new determination of the orbits of the Uranian rings, the orientation of the Uranian pole, and the gravity harmonics of Uranus from the entire set of Uranian ring occultations. Here we report the results of an analysis that redetermined the Uranus and satellite masses, satellite orbits, and the orbit of Uranus. In addition, we obtained a value for the Uranus tidal dissipation factor and produced an independent determination of the Uranian ring orbits, Uranus pole direction, and Uranus gravity harmonics. We also developed new expressions for the orientations of the satellites. We processed all of the data from our previous work plus the new and rereduced astrometry and the ring occultations. We extended our data arc forward to 2016 and backward to 1847. Our new orbit for Uranus is an update of that in ephemeris DE440 incorporating the occultation data and Gaia astrometry.